Spatial Confinement of the Electrical Field Affected by Quantum Effects in Plasmonic Dimer Sandwiching a Single Molecule - Xiaoming Li; Hui Fang; Xiaocong Yuan (IEEE Photonics Journal, 2016)
The spatial confinement of the tip-induced plasmon is a critical factor to determine the resolution of the tip-enhanced Raman spectroscopy (TERS) system. Despite the compressed optical field, only 1 nm is obtained by the self-interaction effect of molecule; however, the deeper physical laws underlying are still under discussion. In addition, due to the gap between the tip and the substrate is only a few nanometers (or less), the quantum effects should be taken into account. For simplicity, we treat the system of the plasmonic dimer with a molecule in the gap as a TERS-like system. In the framework of the newly developed quantum hydrodynamic model, we propose a model to study the light field enhancement and compression affected by the quantum effects in TERS-like system. The results show that the “hot spot” size depends on both the shape and the boundary location of the molecule in the dimer gap. The mechanism of such light field distribution will make us distinguish the boundary of the molecule more clearly. Therefore, our theoretical model offers a new insight into the confinement of the electromagnetic field in the TERS-like system, hence, the physical mechanism of the subnanometer spatial resolution in TERS system.